Effect of inflammation on voriconazole levels in patients with invasive pulmonary aspergillosis - Bakir Ekinci, Pinar; Kara, Emre; Er, Ahmet G; Pinar, Asli; Inkaya, Ahmet C; Demirkan, Kutay; Metan, Gokhan; Uzun, Omrum (The Journal of Infection in Developing Countries, 2024)
Introduction: Voriconazole (VCZ) serum concentrations may be affected by many factors, such as drug-drug interactions, liver dysfunction, genetic polymorphism, and inflammation. This study aimed to determine the relationship between VCZ measured trough plasma levels and C-reactive protein levels in patients with coronavirus disease 2019 (COVID-19)-associated aspergillosis (CAPA) and invasive pulmonary aspergillosis (IPA). Methodology: Patients who were > 18 years of age, received VCZ treatment for IPA or CAPA in our hospital between March 2020 and April 2021, and had their VCZ level monitored, were included in this retrospective study. Results: A total of 85 patients (35 diagnosed with CAPA) were included in this study. Forty-three patients (50.6%) had VCZ levels in the therapeutic range, 4 (4.7%) were sub-therapeutic, and 38 (44.7%) were supra-therapeutic. Inflammatory markers were significantly higher in patients with supra-therapeutic levels (p < 0.05). Supra-therapeutic levels and VCZ-related adverse effects were significantly more frequent in CAPA patients than in IPA patients (p = 0.011 and p = 0.002, respectively). Conclusions: Patients diagnosed with CAPA were more prone to adverse effects and supra-therapeutic VCZ levels. More frequent therapeutic drug monitoring is recommended in this patient population.